Diagnostics of the On-Vehicle Shock Absorber Testing - Piotr Zdanowicz; Marek Guzek (Communications - Scientific letters of the University of Zilina, 2021)
The practical problems that usually come up during the on-vehicle testing of motor car shock absorbers have been discussed. Results of example tests carried out to the EUSAMA standard procedure were compared to the test results obtained with using newer methods, i.e. the phase angle method and half power bandwidth method (HPBM). The issue of incompatibility of the typical excitation applied by diagnostic suspension testers with one that often occurs in the road conditions has also been raised. It has also been shown that the wear of shock absorbers may affect the value of braking deceleration of cars with ABS (anti-lock braking system) when moving on uneven ground. The main objective of the work was to assess usefulness and reliability of various diagnostic methods intended for the on-vehicle testing of car shock absorbers.